Peripheral dose measurements with diode and thermoluminescence dosimeters for intensity modulated radiotherapy delivered with conventional and un-conventional linear accelerator - Kinhikar, Rajesh (Medknow Publications & Media Pvt Ltd, 2013)
The objective of this paper was to measure the peripheral dose (PD) with diode and thermoluminescence dosimeter (TLD) for intensity modulated radiotherapy (IMRT) with linear accelerator (conventional LINAC), and tomotherapy (novel LINAC). Ten patients each were selected from Trilogy dual-energy and from Hi-Art II tomotherapy. Two diodes were kept at 20 and 25 cm from treatment field edge. TLDs (LiF:MgTi) were also kept at same distance. TLDs were also kept at 5, 10, and 15 cm from field edge. The TLDs were read with REXON reader. The readings at the respective distance were recorded for both diode and TLD. The PD was estimated by taking the ratio of measured dose at the particular distance to the prescription dose. PD was then compared with diode and TLD for LINAC and tomotherapy. Mean PD for LINAC with TLD and diode was 2.52 cGy (SD 0.69), 2.07 cGy (SD 0.88) at 20 cm, respectively, while at 25 cm, it was 1.94 cGy (SD 0.58) and 1.5 cGy (SD 0.75), respectively. Mean PD for tomotherapy with TLD and diode was 1.681 cGy SD 0.53) and 1.58 (SD 0.44) at 20 cm, respectively. The PD was 1.24 cGy (SD 0.42) and 1.088 cGy (SD 0.35) at 25 cm, respectively, for tomotherapy. Overall, PD from tomotherapy was found lower than LINAC by the factor of 1.2-1.5. PD measurement is essential to find out the potential of secondary cancer. PD for both (conventional LINAC) and novel LINACs (tomotherapy) were measured and compared with each other. The comparison of the values for PD presented in this work and those published in the literature is difficult because of the different experimental conditions. The diode and TLD readings were reproducible and both the detector readings were comparable.